Control of morphology and formation of highly geometrically confined magnetic skyrmions - Chiming Jin (Nature Portfolio, 2017)
Proposals for skyrmion-based high-density memory devices require an understanding of the formation and shape of skyrmions in confined geometries. Here, the authors use electron holography to image magnetic textures in FeGe nanostripes and explore the parameters governing skyrmion morphology.